Optimizing Smart Tourism in Central Java’s Tourism Ecosystem: The Role of AI and Big Data - Sari, Puspa Novita; Susilo, Arifin Dwi (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
This study aims to analyse the influence of perceptions of the potential of Artificial Intelligence (AI) and the benefits of Big Data on tourists' revisit intention through digital tourism experience in Central Java Province. Within the framework of smart tourism development, digital technology plays a crucial role in shaping tourist loyalty by providing accurate, personalized, and adaptive information. A quantitative approach was employed by distributing questionnaires to 153 respondents who are active users of the Visit Jawa Tengah website. The sampling technique used was purposive sampling, with the criteria being users who accessed the website within the past six months to plan their travel. Data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) via SmartPLS 3. The results show that perceptions of the benefits of Big Data have a positive and significant influence on revisit intention, both directly and indirectly through digital tourism experience as a mediating variable. In contrast, perceptions of AI potential significantly influence the digital tourism experience but do not directly affect revisit intention. These findings highlight that strengthening the quality of Big Data-based information serves as a fundamental pillar in building tourist trust, while AI integration requires further optimization to enhance user engagement. Policy recommendations include the development of AI-based personalized recommendation features, Big Data analytic dashboards, digital literacy training for tourism industry stakeholders, and interactive digital campaigns. The results of this study are expected to provide a strategic foundation for reinforcing a sustainable smart tourism ecosystem at the regional level.